Torsade de pointes associated with long-term antiretroviral drugs in a patient with HIV: a case report - Mu, Xuechun; Duan, Yujiao; Xu, Qiuhua; Wang, Sa; Gao, Guiju; Han, Ning; Zhao, Hongxin (Frontiers in Pharmacology, 2023)
With the improving life expectancy of patients with human immunodeficiency virus (HIV), there is an increasing health concern of potential toxicity and drug interactions of long-term antiretroviral therapies. We describe a female patient with HIV, who was admitted to the emergency department following an unexplained loss of consciousness. This patient had been on antiretroviral therapy comprising tenofovir disoproxil fumarate, lamivudine, and lopinavir/ritonavir for 12 years. Coincidentally, she had been prescribed terfenadine for urticaria recently. After 3 days on this medication, she suddenly lost her consciousness, with a distinctive electrocardiogram alteration characterized by QT prolongation and torsade de pointes. This symptom recurred several times over a span of 2 days. We postulate that the primary instigator was an elevated concentration of terfenadine, which can be traced back to her antiretroviral therapy regimen comprising lopinavir/ritonavir. This drug is known to impede the metabolism of cytochrome P450 3A4 substrates and consequently elevate terfenadine concentrations.